(3ebOeI aj GdGbJUGO GdGSdGej (B/s - (3YhOI, QjGV UGdMs ((3HjQhJ(B: s (3OGQ GdgGOj ddWHGYI hGdfTQhGdJhRjY(B, s, 2005)
(3WHjYI h eUGOQ GdJTQjY aj GdGbJUGO GdGSdGej GVGaI Gdi GdLGfH GdeGdj aj GdGbJUGO GdGSdGej h cPG GdabQ h GdJNda GdGbJUGOj(B, (3GdGfaGb(B, (3GdGfJGL h aj GdGNjQ GdJfejI GdGbJUGOjI(B.s
(3eQGLY U(B.331s
Keywords: (3GbJUGO GSdGejs